Application of Peplau's interpersonal relationship theory combined with case management in rehabilitation of patients after primary percutaneous coronary intervention - Lu, Qin; Chu, Zhenliang; Zheng, Yeping; Shen, Juanqin; Lu, Jingjing; Xu, Jianjiang; Wang, Songchao (Frontiers in Cardiovascular Medicine, 2024)
Objective To explore the effect of Peplau's interpersonal relationship theory (PIRT) combined with case management (CM) on exercise-based cardiac rehabilitation (EBCR), self-efficacy of rehabilitation and risk factors in patients after primary percutaneous coronary intervention (PCI). Methods The convenience sampling method was used to select patients who were admitted to the Department of Cardiology in our hospital from January to October 2022 and received PCI for the first time. Patients were divided into a control group and an intervention group. The control group was given routine treatment and health guidance, including radial artery puncture site care, monitoring of vital signs, informing about medication and dietary precautions, etc. and the intervention group was given PIRT combined with CM. The study was conducted for 3 months. The effect of intervention in the two groups was evaluated by the coronary heart disease risk factor index, EBCR knowledge-attitude-behavior questionnaire and EBCR self-efficacy scale. Results The rate of risk factors control including blood pressure (p < 0.001), low density lipoprotein cholesterol (p = 0.012), smoking cessation (p = 0.031) and exercises (p = 0.021), the scores of EBCR knowledge (p < 0.001), attitude (p = 0.001) and behavior (p < 0.001), and the score of EBCR self-efficacy scale (p < 0.001) in the intervention group were better than those in the control group at 3 months after intervention. Conclusion Peplau's interpersonal relationship theory combined with appropriate case management can effectively control cardiovascular disease in patients after primary PCI.